Legal Protection For Local Communities In Natural Resource Utilization Conflicts: A Literature Review - Dian Wibowo; Harry Sudhana; Hardjito S. Darmojo (Cita konsultindo, 2026)
The escalation of natural resource exploitation often places local communities in a vulnerable position, leading to persistent socio-environmental conflicts. This study aims to analyze the implementation of legal protections for local communities within the context of natural resource utilization and to identify the structural barriers that hinder environmental justice. Using a qualitative descriptive method through a comprehensive documentary study, this research examines various legal frameworks, scholarly discourses, and judicial precedents. The findings reveal a significant